A Study on Some Physical Parameters Related to Image Quality and Radiation Safety in Diagnostic Radiology - Begum, Mahfuza; Mollah, AS; Zaman, MA; Haq, M; Rahman, AKM Mizanur (Journal of Bangladesh Academy of Sciences, 2011)
Different essential radiographic parameters were studied in order to assess radiographic image quality ensuring reduction of radiation exposure in some diagnostic X-ray facilities of Bangladesh. Different parameters for developing and fixing liquid were investigated in order to eliminate improper film processing techniques. General information about intensifying screen, radiography and mammography film was also collected. X-ray tube voltage, output radiation dose and exposure time for diagnostic X-ray machines were tested to achieve significant dose reduction without loss of diagnostic information. It is found that output radiation dose varies in different diagnostic X-ray installations. 70% X-ray installations achieve the recommended value for tube voltage while 87.5% measure the exposure time appropriately. Radiation dose level at patient waiting room, dark room and around control panel was also measured. About 92.5, 85 and 77.5% installations show their results within the acceptance limit at these positions respectively which provide radiation safety for patients, workers and public in diagnostic radiology. DOI: http://dx.doi.org/10.3329/jbas.v35i1.7967 Journal of Bangladesh Academy of Sciences, Vol.35, No.1, 7-17, 2011